2022
DOI: 10.18844/cjes.v17i2.6862
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the lesson study approach to develop teacher professionalism

Abstract: The education system should be designed to help in the preparation of individuals for life in the 21st Century. The purpose of this study is to use the Lesson Study approach in studying the geography of the updated content, to improve the professional competencies of teachers based on the results of students' perception levels. The research methods used included observation, experiment, interview, statistical analysis, comparison, and synthesis. The results exhibited that the Lesson Study approach can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This shows that the stages in implementing the TPACK model based on the Industrial Revolution 4.0 platform can practice TPACK steps based on the Industrial Revolution 4.0 platform. This is in line with Akhwani and Rahayu (2021), who stated that TPACK can be trained to teachers which is one type of knowledge that must be mastered by teachers in the 21st century, although the ability of teachers to integrate all components is not easy (Azhar et al, 2022;Muñoz-Martínez et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…This shows that the stages in implementing the TPACK model based on the Industrial Revolution 4.0 platform can practice TPACK steps based on the Industrial Revolution 4.0 platform. This is in line with Akhwani and Rahayu (2021), who stated that TPACK can be trained to teachers which is one type of knowledge that must be mastered by teachers in the 21st century, although the ability of teachers to integrate all components is not easy (Azhar et al, 2022;Muñoz-Martínez et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…In line with the research conducted by Rini Triasningsih (2015) majoring in Early Childhood Teacher Education, Faculty of Education, Semarang State University with the title The Effect of Academic Qualifications on Teacher Performance at SD Dabin I and IV, Pituruh District, Purwerejo Regency. (Azhar et al, 2022) The results showed that: there was a significant influence between academic qualifications on teacher performance in the research conducted at SD Dabin I and IV, Pituruh District, Purwerejo Regency. This shows the importance of teacher academic qualifications in carrying out a good and correct learning process.…”
Section: Resultsmentioning
confidence: 90%